KONSEP MANAJEMEN LINGKUNGAN UNTUK PENATAAN KAWASAN PANTAI STRATEGIS TEGAL BESAR DI DESA NEGARI, KABUPATEN KLUNGKUNG - Agusinta Dewi, Ni Ketut (Bumi Lestari, 2012)
This research is aimed to set up environmetal management concepts for Tegal BesarStrategic Beach Area ( Kawasan Pantai Strategis Tegal Besar) in Negari Village, Subdistrict ofBanjarangkan, Klungkung Regency (Bali). The concepts is utilized in setting up plan of the areabased on its potentials and environmental characteristics. Based on the field observation, it was foundthat the beach is still intact (asri), however it has got some urgent issues to be handled.Environmental management concetp which is implemented in Tegal Besar Beach can beclassified based on existing major issues found, through the concept on environmental conservation ,and on land and space management. For operational of this concept, the role of local community, thegovernment, and private sectors are very important
Keywords: environmental management, conservation,land and space, beach area.